2020
DOI: 10.18632/aging.102730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidants on the H2O2-induced premature senescence of human fibroblasts

Abstract: The study was aimed at evaluation of the role of secondary oxidative stress in the stress-induced premature senescence (SIPS) of human fibroblasts induced by H2O2. Two fibroblast lines were used: lung MRC-5 and ear H8F2p25LM fibroblasts. The lines differed considerably in sensitivity to H2O2 (IC50 of 528 and 33.5 µM, respectively). The cells were exposed to H2O2 concentrations corresponding to IC50 and after 24 h supplemented with a range of antioxidants. Most of antioxidants studied slightly augmented the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…It has been shown that p-CA can have beneficial effects on skin aging by decreasing collagenase, elastase, and hyaluronidase activity [ 386 ], and by reducing the inflammatory response and chondrocytes senescence, inhibiting MAPK and NF-kB signalling pathways [ 327 ]. However, although some works have demonstrated the antioxidant property of p-CA, Pieńkowska et al highlighted that this acid is unable to counteract the premature senescence of human fibroblasts [ 387 ]. Consequently, the presence of contradictory evidence in literature requires further research.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that p-CA can have beneficial effects on skin aging by decreasing collagenase, elastase, and hyaluronidase activity [ 386 ], and by reducing the inflammatory response and chondrocytes senescence, inhibiting MAPK and NF-kB signalling pathways [ 327 ]. However, although some works have demonstrated the antioxidant property of p-CA, Pieńkowska et al highlighted that this acid is unable to counteract the premature senescence of human fibroblasts [ 387 ]. Consequently, the presence of contradictory evidence in literature requires further research.…”
Section: Resultsmentioning
confidence: 99%
“…The previously published reports demonstrated that the dermal fibroblasts receiving H 2 O 2 underwent G0/G1 arrest. This cellular adaptation was also observed concomitantly with ROS accumulation and oxidation-associated damage [ 10 , 11 ]. In this regard, oxidative stress could result in DNA damage and cell cycle arrest [ 6 ].…”
Section: Discussionmentioning
confidence: 95%
“…Senescent fibroblast cells have a specifically enlarged cytoplasm, poor response to growth factors, and β-galactosidase activity [ 4 , 23 , 24 ]. The H 2 O 2 , when being exposed to cultured fibroblasts, induces premature senescence by imposing oxidative stress and sustained accumulation of oxidative DNA damage [ 10 , 11 ]. In this study, the preventive ability of nuciferine to mitigate H 2 O 2 -induced premature senescence was assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations